Simulation design of P–I–N-type all-perovskite solar cells with high efficiency - 杜会静 王韦超 顾一帆 (Chinese physics B, 2017)
According to the good charge transporting property of perovskite, we design and simulate a p–i–n-type all-perovskite solar cell by using one-dimensional device simulator. The perovskite charge transporting layers and the perovskite absorber constitute the all-perovskite cell. By modulating the cell parameters, such as layer thickness values, doping concentrations and energy bands of n-, i-, and p-type perovskite layers, the all-perovskite solar cell obtains a high power conversion efficiency of 25.84%. The band matched cell shows appreciably improved performance with widen absorption spectrum and lowered recombination rate, so weobtain a high J_（sc） of 32.47 m A/cm~2. The small series resistance of the all-perovskite solar cell also benefits the high J_（sc）. The simulation provides a novel thought of designing perovskite solar cells with simple producing process, low production cost and high efficient structure to solve the energy problem.